2009
DOI: 10.1111/j.1440-1681.2008.05089.x
|View full text |Cite
|
Sign up to set email alerts
|

A BIOAVAILABILITY/BIOEQUIVALENCE AND PHARMACOKINETIC STUDY OF TWO ORAL DOSES OF TORASEMIDE (5 AND 10 mg): PROLONGED‐RELEASE VERSUS THE CONVENTIONAL FORMULATION

Abstract: 1. The main objective of the present study was to compare the bioavailability/bioequivalence of a new prolonged-release (PR) formulation of torasemide with an immediate-release (IR) formulation. In addition, we assessed the pharmacokinetics of both formulations, as well as the urine pharmacodynamics. 2. Two doses (5 and 10 mg) of PR torasemide were compared with the same doses of IR torasemide in a single-blind, single-dose, two-treatment, two-period, cross-over, sequence-randomized clinical trial in 20 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…One was abandoned and the other improved antihypertensive efficacy only modestly and failed to improve fluid or electrolyte excretion likely because it prolonged the time to reach peak serum concentration only slightly. [34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…One was abandoned and the other improved antihypertensive efficacy only modestly and failed to improve fluid or electrolyte excretion likely because it prolonged the time to reach peak serum concentration only slightly. [34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…In the study by López et al, mean serum concentrations of PICP at the end of the study were 111 µg/l in the torasemide-IR group and 133 µg/l in the furosemide group, with a punctual estimation of the size effect of 22 µg/l (95% CI: 7-37) [30]. Standard errors in both groups of 19 and 17 cases were 3 and 7 µg/l, respectively, with a punctual estimation of the standard error of 22 (95% CI: [18][19][20][21][22][23][24][25][26][27][28][29]. If a difference between treatment of 15 µg/l and a standard error of 29 (both values included in their 95% CIs) are considered as clinically relevant, the sample size required at the a = p < 0.05 (two-sided) and a power (1-b) of 80% is 59 patients per group (a total of 118).…”
Section: Power Calculation and Sample Sizementioning
confidence: 99%
“…In addition, torasemide-IR has a longer half-life and duration of action, and higher bioavailability compared with furosemide [23]. A new, recently developed torasemide prolonged-release (PR) formulation has shown lower peak plasma levels while maintaining equivalent AUC of plasmatic levels compared with the IR formulation [24][25][26]. Moreover, a recent randomized noninferiority trial demonstrated that both PR and IR torasemide formulations were well tolerated and showed similar efficacy, tolerability and safety profiles in a population of mild-to-moderate hypertensive patients [27].…”
mentioning
confidence: 99%
“…It is postulated that, compared with furosemide, torasemide reduces readmissions due to heart failure [6]; moreover, there is a discussion of its possible beneficial effect on mortality [7]. Yet torasemide has been shown to have less inter- and intra-individual variation in bioavailability and longer action than furosemide [8]. Vargo et al reported that heart failure does not affect the rate of absorption of orally administered torasemide, in contrast with furosemide, for which absorption was delayed [9].…”
Section: Introductionmentioning
confidence: 99%
“…Torasemide also induces greater improvements in functional and social limitations. Some clinical studies showed improvement in New York Heart Association (NYHA) functional class and pulmonary haemodynamics, as well as reduced body weight, in patients who received torasemide [8, 11, 12]. In a study by Müller et al , torasemide decreased the number of mictions at 3, 6 and 12 h after diuretic intake, as well as the urgency to urinate [11].…”
Section: Introductionmentioning
confidence: 99%